Genomics: Applications to Antarctic ecosystems - Peck, L; Clark, MS; Clarke, A; Cockell, C; Convey, P; Detrich, H; Fraser, K; Johnston, I; Methe, B; Murray, A; Römisch, K; Rogers, A (2005)
Biological research in Antarctica has made considerable progress in science over recent decades. As little as 50 years ago, there was scant knowledge even of the species inhabiting the region. Since then, understanding has developed rapidly, across diverse disciplines including physiology, biochemistry, ecology and biogeography. Some dramatic global-scale discoveries and advances have been made, including the characterisation of antifreeze proteins from notothenioid fish and the finding that some fish lack a heat shock response, the identification of microbial communities living within the surface layers of rocks and description of the simplest faunal communities known, the identification that possibly the fastest environmental and ecological change on earth is occurring in Antarctic lakes, and that the biodiversity of the Southern Ocean is much greater than previously thought. Findings such as these have made biology in cold extreme environments one of the most stimulating areas for research in recent decades. Now, the advent and widespread applicability of the novel genomic technologies promise to move us into a period of equally, or possibly even more, rapid advance. At present, genomic information on Antarctic species is limited mainly to a number of fish species and microbes. However, an increasing number of Antarctic genomics projects are being funded and will significantly increase the amount of molecular information available on a much wider range of species in the near future. Hence it is timely to review progress so far in the use of genomic methods in Antarctic research and identify exciting prospects for dramatic future advances. © Springer-Verlag 2004.